ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DALAM LAPORAN TAHUNAN PERUSAHAAN (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia) - Winda Kurnia (Jurnal Ilmiah Mahasiswa FEB, 2018)
This study aims to obtain empirical evidence about the influence of board size,profitability, media exposure, and company age on disclosure of Corporate SocialResponsibility. The population in this study included banking companies listed on theIndonesia Stock Exchange in 2016-2017. The sampling technique uses purposivesampling. The study samples are 35 companies, with two years of observation. So thetotal samples are 70. The analysis method used is multiple regression.The results ofthis study indicate that the size of the board of commissioners, profitability, and ageof the company influence the disclosure of Corporate Social Responsibility. While themedia exposure variable did not affect the disclosure of Corporate SocialResponsibility. The results of this study are expected to be a material consideration inimproving the implementation of disclosure of Corporate Social Responsibility in thecompanyKeywords: Corporate Social Responsibility disclosures, size of the board ofcommissioners, profitability, media exposure, company age